Wacana Gender dan Relasi Kuasa dalam Cerpen Kuzuha No Issei Karya Matsuda Aoko - Maghfira, Cahya Tahta; Purba, Esther Risma (Humanis; Vol 27 No 2 (2023)DO - 10.24843/JH.2023.v27.i02.p01, 2023)
This study aims to analyze the issues of gender gap in contemporary Japanese society that represented in the short story of Kuzuha no Issei, along with the things that had been became the roots of these problems. Because the issue of gender gap was influenced by social constructions and stereotypes, this study will use a general gender theory approach and associated with Michael Foucault’s power relations. The result shows there are six gender gap issues that arise in the short story of Kuzuha no Issei. That was ‘women should not stand out’, ‘women and simple jobs’, ‘someone ability was judged by gender’, ‘women as housewives’, ‘demure Japanese women’, and ‘women and men as the victims of government discourses’. This phenomenon was influenced by the patriarchal system, IE, traditional gender stereotypes such as ry?sai kenbo and yamato nadeshiko, as well as the discourses in Japanese society which had been normalized to form doctrines and social constrctions.    Penelitian ini bertujuan menganalisa isu-isu kesenjangan gender di tengah masyarakat Jepang kontemporer dalam cerita Kuzuha no Issei, beserta hal-hal yang menjadi akar dari permasalahan tersebut. Karena isu kesenjangan gender ini dipengaruhi oleh konstruksi dan stereotip sosial, maka digunakan pendekatan kritis dengan teori gender dan dikaitkan dengan relasi kuasa dari Michael Foucault. Hasil penelitian ini menunjukkan terdapat enam isu kesenjangan gender dalam cerita Kuzuha no Issei, yaitu perempuan tidak boleh menonjol, perempuan dan pekerjaan sederhana, kemampuan seseorang dinilai berdasarkan gender, perempuan sebagai ibu rumah tangga, perempuan harus menjaga sikap, serta perempuan dan laki-laki sebagai korban diskursus pemerintah. Fenomena ini dipengaruhi oleh sistem patriarki, IE, stereotip gender tradisional seperti ry?sai kenbo dan yamato nadeshiko, serta diskursus dalam masyarakat yang dinormalisasi sehingga membentuk doktrin dan konstruksi sosial.